The Influence of Recycled Coarse Aggregate Content on the Properties of High-Fly-Ash Self-Compacting Concrete - Nguyen, Hung Cuong (Civil Engineering Journal, 2024)
In Vietnam, solid waste from construction activities significantly impacts environmental pollution. Recycled concrete aggregate (RCA), derived from waste concrete, can serve as a coarse aggregate in concrete production. However, compared to natural aggregates, RCA exhibits distinct characteristics, including lower strength, higher water absorption, and an increased angular and rough surface. These properties may influence concrete’s workability, compressive strength, and durability. This research investigates the influence of RCA on the properties of High-Fly-Ash Self-Compacting Concrete (SCC). The study explores various replacement levels of natural coarse aggregate with RCA (0%, 50%, 75%, and 100%), alongside a 50% volume fraction of fly ash. Key concrete properties evaluated include workability, compressive strength, flexural strength, and chloride ion permeability. The findings reveal that using 100% RCA in combination with a high fly ash content (50%) produces SCC that meets workability requirements according to EFNARC standards. However, there are trade-offs: the compressive strength decreases by 4.61%, the flexural strength decreases by 3.1%, and chloride ion permeability increases by 57.57% compared to the control sample (using natural aggregates). Notably, the chloride ion permeability of SCC using 100% RCA falls into the category of low permeability. Doi: 10.28991/CEJ-SP2024-010-04 Full Text: PDF